Determinan Implementasi Central Bank Digital Currency di Indonesia - Widodo, Kharisma Dwi; Juanda, Bambang; Hakim, Dedi Budiman (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Private digital currency is no longer limited to shadow banking issues but has also entered shadow central banking, putting Bank Indonesia to adopt the CBDC. This study aims to determine the effect of macroeconomic, accessibility, and demographic aspects on CBDC implementation, as well as the impact of publicity on changes in the behavior of economic actors in using CBDC in Indonesia. The results of the study show that GRDP, gini ratio, ICT, and bank accounts have an effect on CBDC. Publicity affects changes in the behavior of economic actors in increasing the conversion of fiat money to CBDC.